2013
DOI: 10.1007/s11682-012-9220-1
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor MRI of chemotherapy-induced cognitive impairment in non-CNS cancer patients: a review

Abstract: Patients with non-central nervous system cancers often experience subtle cognitive deficits after treatment with cytotoxic agents. Therapy-induced structural changes to the brain could be one of the possible causes underlying these reported cognitive deficits. In this review, we evaluate the use of diffusion tensor imaging (DTI) for assessing possible therapy-induced changes in the microstructure of the cerebral white matter (WM) and provide a critical overview of the published DTI research on therapy-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 232 publications
0
72
0
2
Order By: Relevance
“…A recent cross-sectional investigation provided evidence for hippocampal damage that was related to decreased verbal memory performance [29]. In line with the findings from the animal work reported above, diffusion tensor imaging (DTI) studies have found chemotherapy-related reductions of white matter integrity that correlated with cognitive performance [30]. A prospective DTI study Paradigms included verbal long-term memory [37,38], verbal working memory [39,40], and tasks requiring rule testing or planning, both involving prefrontal cortex [41,42].…”
Section: Manymentioning
confidence: 75%
“…A recent cross-sectional investigation provided evidence for hippocampal damage that was related to decreased verbal memory performance [29]. In line with the findings from the animal work reported above, diffusion tensor imaging (DTI) studies have found chemotherapy-related reductions of white matter integrity that correlated with cognitive performance [30]. A prospective DTI study Paradigms included verbal long-term memory [37,38], verbal working memory [39,40], and tasks requiring rule testing or planning, both involving prefrontal cortex [41,42].…”
Section: Manymentioning
confidence: 75%
“…Recent studies have documented that chemotherapy can disrupt hippocampal neurogenesis (Dietrich et al 2006), and is associated with alterations in white matter integrity (Inagaki et al 2007; Deprez et al 2013). Recent rodent studies have shown that cisplatin inhibits neurogenesis and disrupts cognitive function (Manohar et al 2014; Vichaya et al 2015), and that metformin may prevent cisplatin-related central neurotoxicity (Zhou et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…DTI measurements show strong correspondence with post-mortem dissection (Lawes, et al, 2008) however; DTI should be considered only a very indirect assessment of white matter organization (Jones, et al, 2013). Despite its limitations, DTI-based measures have been shown to be sensitive to various brain pathologies, including breast cancer-related cognitive impairment (Deprez, et al, 2013). …”
Section: Introductionmentioning
confidence: 99%